The Mass Media in Extension: A Review of Recent Literature - Jack C. Everly (Journal of Applied Communications, 1971)
A new thrust for the 1970's is noted in the current research and evaluative efforts of Cooperative Extension personnel as they try to assess the role of mass media in expanded areas of work.